Sob o olhar da Santa Madre: articulações entre a vida de Santa Veronica Giuliani e a clínica da anorexia - Weinberg, Cybelle (2015)
Under the eye of the Holy Mother: articulations between the life of Saint Veronica Giuliana and the anorexia clinic aims at relating facts from the life of Saint Veronica, who lived in Italy in the late 17th century and the early 18th century, with today s anorexia clinic. The analysis of her diaries and the registers in her canonization process show how much her perseverant life style, marked by periods of intensive fasting, the violence against her own body, and her search for holiness under the benevolent eye of the Church associates her with modern anorexic symptoms. This paper aims at setting up a parallel between two kinds of relationship: that of Christianity s women saints and martyrs with the Church (the Holy Mother), and that of anorexic girls with their mothers. Accomplices of a lethal project, these pairs comply with the appealing of a perfection ideal. Although separated by several centuries, they present the same symptoms and manifestations of a timeless superego that is passed down from generation to generation. The analysis of such lives marked by excess reveals how an Ideal that was born and built up at the beginning of the western medieval era transcends time and is revealed by people s singularity